Constituents of essential oil from the zhizomes of Siliquamomum tonkinense Baill. collected in Tam Dao national park , Vinh Phuc province - Thanh, Bui Van; Binh, Nguyen Quoc (Academia Journal of Biology, 2015)
The genus Siliquamomum Baill. comprises only two species, viz., Siliquamomum tonkinense Baill. and Siliquamomum oreodoxa N.S. Glass & Skornick., The species S. tonkinense was used as traditional medicinal plant for treat stomach pain, stomach bleeding or medicinal bath for women after childbirth. The essential oil from the rhizomes of S. tonkinense collected in Tam Dao National Park, Vinh Phuc province (Vietnam) was prepared by steam distillation of fresh material for 3h. The essential oil was obitained in 0.37% yield from the rhizomes (in absolute dry state). The essential oil from S. tonkinense analyzed by GC/MS consists of 42 constituents, accounting for more than 96.18% of the oil content. The major components of the essential oil from the rhizomes of S. tonkinense are: 1,8-cineol (31.78%), E-E-farnesol (10.62%), Myrtenal (8.10%), Borneol (6.64%), β-pinen (5.21%), γ-terpinen (4.82%), 0-cymen (3.89%), 7-epi-α-selinen (2.20%), α-terpineol (2.14%). Eight components were accounted for 1.04 to 1.88% and all the rest components have content less than 1.00%. Keywords: Siliquamomum tonkinense, 1,8-cineol, essential oil, Tam Dao National Park.